2013
DOI: 10.17221/6825-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary phenylpropanoid glycoside-based natural extracts on blood parameters and productive performance in intensively-reared young hares

Abstract: ABSTRACT:Two different doses of a dietary verbascoside-based supplement were evaluated on various blood parameters and on productive performance in young weaned hares reared intensively from 28 to 90 days of age. The study lasted for 62 days and it was conducted on 210 young hares divided into three homogeneous groups of 70 animals each, consisting of a control group and two experimental groups. Each group received the dietary supplement in the feed, titrated to 0.5% verbascoside, 1 kg/t of concentrate (LVB gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
5
15
0
1
Order By: Relevance
“…The results on blood lipid profile, observed in rabbits fed with PLX ® 23 and LycoBeads ® , are in agreement with what was highlighted in previous researches, about rabbits Casamassima, Palazzo, Vizzarri, Costagliola, et al, 2013), ovine (Casamassima et al, 2012;Casamassima, Palazzo, D'Alessandro, et al, 2013) and hare (Casamassima, Palazzo, Vizzarri, Cinone, & Corino, 2013;Palazzo et al, 2011) (Fuhrman et al, 1997) and the activity of up-regulation in macrophage LDL receptor (Arab & Steck, 2000), as well as to its high power to neutralize free radicals.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results on blood lipid profile, observed in rabbits fed with PLX ® 23 and LycoBeads ® , are in agreement with what was highlighted in previous researches, about rabbits Casamassima, Palazzo, Vizzarri, Costagliola, et al, 2013), ovine (Casamassima et al, 2012;Casamassima, Palazzo, D'Alessandro, et al, 2013) and hare (Casamassima, Palazzo, Vizzarri, Cinone, & Corino, 2013;Palazzo et al, 2011) (Fuhrman et al, 1997) and the activity of up-regulation in macrophage LDL receptor (Arab & Steck, 2000), as well as to its high power to neutralize free radicals.…”
Section: Discussionsupporting
confidence: 92%
“…The results on blood lipid profile, observed in rabbits fed with PLX ® 23 and LycoBeads ® , are in agreement with what was highlighted in previous researches, about rabbits (Casamassima et al, ; Casamassima, Palazzo, Vizzarri, Costagliola, et al, ), ovine (Casamassima et al, ; Casamassima, Palazzo, D’Alessandro, et al, ) and hare (Casamassima, Palazzo, Vizzarri, Cinone, & Corino, ; Palazzo et al, ) fed‐supplemented with VB. Even Lorenz et al (), feeding rabbits with a high‐cholesterol diet, and daily supplementing for 4 weeks 5 mg of lycopene per kg of live weight, observed a reduction of about 50% of the blood concentration of total cholesterol and LDL cholesterol, when compared to the placebo group and the high‐fat diet group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the Verbenaceae family, verbascoside (VB) is the most abundant phenolic compound, with higher antioxidant activity compared to the other substances . Several studies in farm animals, reported the in vivo antioxidant properties of VB . Recent studies reported an improvement of meat quality parameters of broiler and pig fed plant extract, containing verbascoside …”
Section: Introductionmentioning
confidence: 99%